(untitled) (Indonesian Journal of Agrarian Law, 2026)
Through the inventory and identification procedure conducted by the Klaten Regency Land Office, this study seeks to analyse the application of land management indicated by abandonment in achieving legal certainty of the status of land rights and averting land disputes. This research is motivated by the fact that the use of land is still inconsistent with the purpose for which the rights were granted, thereby creating the potential for legal uncertainty and conflicts in land tenure. The research uses an empirical juridical approach with a qualitative descriptive method through document studies, interviews, and field observations. The results of the study show that the implementation of the land inventory indicated to be abandoned by the Klaten Regency Land Office has been carried out based on the provisions of Government Regulation Number 20 of 2021, through the stages of data collection, verification, field monitoring, and report preparation. However, the effectiveness of its implementation still faces various obstacles, such as limited administrative data, lack of coordination between agencies, limited resources, low participation of rights holders, and land ownership by other parties. However, inventory activities have implications for increasing legal certainty and have a preventive function in preventing potential disputes by providing clarity on the status and use of land. Therefore, it is necessary to strengthen data integration, cross-sector coordination, and increase public legal awareness to support the optimization of abandoned land management.